Corticosteroid Injections Into Lumbar Facet Joints: A Prospective, Randomized, Double-Blind Placebo-Controlled Trial. (October 2018) - Kennedy, David J.; Huynh, Lisa; Wong, Joe; Mattie, Ryan; Levin, Josh; Smuck, Matthew; Schneider, Byron J.
Abstract : Background: Corticosteroid injections into the intra-articular zygapophysial (z-joints) are frequently used to treat this cause of low back pain. No studies have been done on the efficacy of intra-articular corticosteroids in those with z-joint pain confirmed by dual comparative medial branch blocks. Objective: The aim of the study was to determine whether an injection of a corticosteroid into lumbar z-joints is effective in reducing pain and the need for radiofrequency neurotomy. Methods: This is a double-blind, prospective, randomized, placebo-controlled trial. The study was conducted in Academic Medical Center. Twenty-eight subjects with z-joint pain confirmed by medial branch blocks were included in the study. Subjects with confirmed z-joint pain via dual comparative medial branch block were randomized to receive either intra-articular corticosteroid (triamcinolone 20 mg) or saline via fluoroscopic guided injection. Results: No statistically significant difference in the need for radiofrequency neurotomy (radiofrequency neurotomy) between the groups, with 75% (95% confidence interval = 50.5%–99.5%) of the saline group vs. 91% (95% confidence interval = 62.3%–100%) of the corticosteroid group receiving radiofrequency neurotomy. There is no difference in mean time to radiofrequency neurotomy between saline (6.1 wks) and corticosteroid (6.5 wks) groups. There is a need for radiofrequency neurotomy. Conclusions: Corticosteroid injections into the lumbar z-joints were not effective in reducing the need for radiofrequency neurotomy of the medial branches in those with z-joint pain confirmed by dual comparative medial branch blocks. Abstract : Supplemental digital content is available in the text.